LABORATORY PERFORMANCE OF HOT ROLLED SHEET (HRS-WC) USING BUTON GRANULAR ASPHALT AND RETONA BLEND 55 - ANGGREINI (NIM 26906006), LIA
Mixture resistance to plastic deformation, heavy traffic and high temperature is the object of the important research on pavement materials. The result of some previous research shows that the addition of Asbuton in the asphalt mixture can increase the value of Dynamic Stability, give good resistance of rut depth and increase the value of Resilient Modulus. The objectives of this study was to asses the mixture performance of HRS-WC using 5% Buton Granular Asphalt (BGA) and using Retona blend 55 that will be compared with HRS-WC mix using Pen 60/70. A further test was done to find the resistance of the mixture against permanent deformation and the Mix Stiffness by using Wheel Tracking test and UMATTA. Retona Blend 55 gives the highest resistance to water damage (98,13%), which is shown by IRS (Index Retained Strength of Marshall) value, compared to Buton Granular Asphalt (Pen 60/70+BGA 5%) mixture (91,92%) and Pen 60/70 mixture (86,41%). The result of Wheel Tracking test showed that the addition 5% BGA and Retona Blend 55 can increase the value of Dynamic Stability. The highest value of Dynamic Stability at temperature 45oC and 60oC was obtained by the Retona Blend 55 mixture (12.600 & 4.200 passes/mm), compared to the Pen 60/70+BGA 5% mixture (10.500 & 1.050 passes/mm) and Pen 60/70 mixture (7.000 & 2.032,3 passes/mm). However at temperature 60oC, the Dynamic Stability value of Pen 60/70+BGA 5% mixture was lower than the Pen 60/70 mixture. Comparing the Stiffness Modulus measured by the UMATTA test and the Stiffness Modulus calculated by the SHELL formula, it is shown that at temperature 45oC and 60oC, Retona Blend 55 gave the highest value of Resilient Modulus (1679 MPa & 931,3 MPa), compared to the Pen 60/70+BGA 5% mixture (1127 MPa & 508,5 MPa) and the Pen 60/70 mixture (902,9 MPa & 404,0 MPa). But the Resilient Modulus value of Pen 60/70 mixture was higher than Pen 60/70+BGA 5% mixture, based on SHELL's formula. Generally, Hot Rolled Sheet-Wearing Course (HRS-WC) mixes with the addition of Retona Blend 55 gives the best result compared to the others, which is shown by the value of Index Retained Strength of Marshall, the value of Dynamic Stability and its Resilient Modulus.